Synergy Between Parents and Teachers in Optimising the 8 Multiple Intelligences of Early Childhood: A Collaborative Study in Kindergarten - Pulung Revastianto; Suyadi Suyadi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This research aims to analyse the role of parents and teachers in developing multiple intelligences in early childhood, focusing on the importance of collaboration between both parties. The methodology used in this research is a qualitative approach through literature study, observation, and interviews. The results show that the synergy between parents and teachers is highly influential in creating a learning environment that supports the development of various types of children's intelligence. This research affirms that parents should not generalise the abilities and intelligence of each child, but rather understand and appreciate individual differences. Moreover, the active role of parents as motivators and facilitators at home, as well as the role of teachers in designing innovative teaching methods, has proven effective in enhancing children's multiple intelligences. These findings provide important insights for the development of early childhood education that is more inclusive and responsive to students' individual needs.